The Influence of Non-Physical Special Allocation Funds in the Health Sector in Improving the Implementation Calibration of Medical Devices Public Health Centers in Indonesia - Damayanti, Wulan Sri; Bashabih, Masyitoh (Poltekkes Kemenkes Palu, 2024)
The quality of health services at the health center is greatly influenced by health equipment. Efforts to maintain health equipment so that it functions properly and is suitable for use include carrying out maintenance including calibration of medical devices. In 2022, the calibration achievement of health centers is still very low compared to the achievement of hospital calibration (health centers 34.1% and hospitals 70.2%). One of the factors causing the low calibration implementation is the lack of budget availability. In 2023, the government provided budget support for health center calibration through the Health Sector Nonphysical Special Allocation Fund. This study aims to determine the achievement of the implementation of medical device calibration at health centers in Indonesia in 2022 and 2023 and the effect of the Nonphysical Special Allocation Fund for the health sector in 2023 on improving the implementation of calibration at health centers. This study is a quantitative study with a cross-sectional design. Data collection used secondary data with a total sampling of 10,374 health centers. Data analysis techniques were carried out univariate and bivariate using SPSS. Univariate analysis showed an increase in the proportion of health centers that calibrated medical devices by 22.6% from 34.1% in 2022 to 56.7% in 2023. Similarly, the proportion of calibrated medical devices increased by 3.5% from 6.6% in 2022 to 11.6% in 2023. Bivariate analysis using the T-test obtained a p-value = 0.008 and the Chi-Square test obtained a p-value = 0.002, indicating an association between the Nonphysical Special Allocation Fund for the Health Sector and the increase in the calibration achievement of puskesmas in 2023.